Konstruksi Kalimat Transitif dalam Berita Daring Merdeka.COM Edisi Januari 2019: Kajian Lexical Functional Grammar - Invandri Kusuma (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
This study examines the syntactic nature of the transitive sentence construction in the January 2019 edition of Merdeka.com online news. The sentence construction in this study is influenced by the affixation process. The affixation process changes the structure into several different arguments from before. While obscene arguments often occur to hide objects or actors as objects. Argument based Lexical Functional Grammar analysis based on structure takes into account the complex nature of unusual structures. Provision of data using the listen method and in analyzing data using the distribution distribution method. The data is sourced from the use of sentences in Merdeka.Com online news in writing. The results of this study verbs undergo an affixation process on the predicate function to determine their arguments. Some words do not undergo the process of affixation to form more than two arguments. The same subject in the parent sentence and clause form the X-Comp in the formal word. Keywords: Transitive Sentences, Lexical Functional Grammar, Online News, Verbs